Penerapan Penerapan Metode Outdoor Study untuk Menumbuhkan Karakter Peduli Lingkungan pada Siswa Sekolah Dasar - Ismi Anggraini (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Environmental degradation highlights the importance of fostering environmental awareness from an early age. This study examines the implementation of the outdoor study method and its effectiveness in developing environmental care among elementary school students. Using a descriptive qualitative literature review, data were collected from journals, books, and conference proceedings and analyzed through thematic content analysis. The findings show that outdoor study activities, such as ecosystem observation, school gardening, and waste management, improve students' environmental knowledge, empathy, responsibility, and sustainable behaviors. In conclusion, outdoor study effectively connects classroom learning with real-life experiences and strengthens environmentally responsible character in elementary school students